2006
DOI: 10.1380/ejssnt.2006.129
|View full text |Cite
|
Sign up to set email alerts
|

XPS study of ultrathin carbon films prepared by filtered cathodic vacuum arc

Abstract: Diamond like carbon (DLC) films have attracted increasing attention in a variety of industries due to their excellent mechanical and chemical properties. To meet the demands from the emerging industries, such as micro electro mechanical systems (MEMS), a considerable number of research studies have been conducted to advance the technology for thin DLC films fabrication. However, it has been reported that the properties of DLC films vary with thickness, which necessitate further understanding of the mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The nano-indentation hardness was not significantly high in regions with high hydrogen content, even when the sp 3 ratio was large. Thus, it was difficult to predict the properties of amorphous carbon by estimating the sp 3 ratio using NEXAFS, X-ray photoelectron spectroscopy (XPS) [ 89 , 90 , 91 ], and electron energy-loss near-edge structure [ 92 ]. Importantly, the estimation of hydrogen content played a crucial role in characterizing amorphous carbon.…”
Section: Sp 3 Ratio-hydrogen Content-based Clasmentioning
confidence: 99%
“…The nano-indentation hardness was not significantly high in regions with high hydrogen content, even when the sp 3 ratio was large. Thus, it was difficult to predict the properties of amorphous carbon by estimating the sp 3 ratio using NEXAFS, X-ray photoelectron spectroscopy (XPS) [ 89 , 90 , 91 ], and electron energy-loss near-edge structure [ 92 ]. Importantly, the estimation of hydrogen content played a crucial role in characterizing amorphous carbon.…”
Section: Sp 3 Ratio-hydrogen Content-based Clasmentioning
confidence: 99%
“…In this present study, the structure of the 200-nm-thick film can be modeled same as a hydrogen-free ta-C film from the work of Yasui et al [23]. They reported that the hydrogen-free ta-C film deposited by the FCVA method exhibits two sublayers known as sp 2 -rich surface layer and sp 3 -rich layer located below this sp 2 -rich surface layer.…”
Section: Tablementioning
confidence: 84%
“…In the FCVA method, the energy distribution of the carbon ions in the cathodic arc discharge has a wide range. The irradiation of high-energy ions during deposition contributes to film growth by forming a sp 3 -rich bulk layer, while low-energy ions resulted in the formation of a soft surface layer with high sp 2 bonding [23].…”
Section: Tablementioning
confidence: 99%
“…The graphite target was sputtered by Ar plasma at an RF power of 200 W, an Ar mass flow rate of 50 seem, and a pressure during the sputtering of 0.6 Pa. In the case of sputtering, the depositing atoms have an energy of several eV, i.e., lower than that in FCV A [7], which leads to lower s/ bonding ratio in the film [5].…”
Section: Methodsmentioning
confidence: 99%
“…The present study aims to verify the relationship between the increase in COF and the various froperties that change with film thickness, such as the sp ratio [5], surface roughness, and thickness itself, under a normal load, which does not cause explicit plastic deformation on the surface, and finally identify the critical parameter 523 that accounts for nano-tribological behavior of ultrathin DLC films.…”
Section: Introductionmentioning
confidence: 99%